Rapid dilution effectively decreases hydrocarbons following small oil spills, but impacts on microeukaryote communities are still observed - Ortmann, Alice C.; Poon, Ho Yin; Ji, Meng; Cobanli, Susan E.; Wohlgeschaffen, Gary; Greer, Charles W.; Robinson, Brian; King, Thomas L. (Frontiers in Marine Science, 2024)
Dilution affects the distribution and weathering of oil following a spill into coastal seawater, but including dilution in experiments is rare. In open water, dilution is expected to rapidly reduce the concentrations of hydrocarbons, and estimates of impacts and microbial responses from batch experiments may overestimate what happens during a spill event. Three experiments carried out in the southern Gulf of St. Lawrence incorporated periods of incubation of natural microbial communities with either Heidrun medium crude or Bunker C fuel oil followed by dilutions using unexposed seawater. Higher concentrations of n-alkanes (C10 – C35) in Heidrun, resulted in higher initial total hydrocarbon concentrations in incubations with Heidrun compared to Bunker C. Similar polycyclic aromatic hydrocarbon concentrations and potential toxicity were measured in the water column for both oils. Dilution effectively decreased the hydrocarbon concentrations, reducing them to background levels after two dilutions (13.8-fold). Neither the abundance nor the diversity of the prokaryote community was strongly affected by the addition of oil. The natural coastal microbiome was dominated by bacteria that may be facultative hydrocarbon degraders. The abundance of phytoplankton and the diversity of the microeukaryote community decreased during the second incubation in response to both Heidrun and Bunker C, potentially due to photooxidative byproducts produced under full sunlight. Dilution appears to limit the bacterial response to oil, but low hydrocarbon concentrations may still be linked to impacts on the microeukaryote community.